A study of effect of delayed and early umbilical cord clamping on neonatal haemoglobin status - Jaiswal, Jyoti; Dehariya, Krishna Kumar; Nagraj, Devina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Delayed cord clamping has been supported by physician because it allows for physiological transfer of blood from placenta to the infant and thus permits placenta to newborn transfusion and results in an increased neonatal blood volume at birth. At present there is no standard definition of delayed cord clamping. Clamping time varies significantly between studies and a wide range of parameters were used for clamping of cord. Methods: This was an observational study conducted in a public hospital among 200 uncomplicated full-term pregnancies where 100 each were present in early cord clamping (ECC) and delayed cord clamping (DCC) groups respectively and neonatal haematological parameters studied according to different cord clamping times. Results: There was a significant increase of mean haemoglobin level from 14.8 to 16.0 g/dl from 15 secs to 60 secs and gradual increase of mean haemoglobin level from 16.2 to 16.8 g/dl from 60 secs to 180 secs. There was a highly significant difference between ECC and DCC groups regarding mean haemoglobin level and MCH values. MCV and MCH values were also significantly different in both the groups. Conclusions: We concluded in this study that delayed cord clamping, resulted in improved haemoglobin and other haematocrit levels specially when cord was clamped after first 60 secs. Delayed clamping also reduced the prevalence of neonatal anaemia at 2 days of age. In terms of maternal outcomes, delayed umbilical cord clamping did not increase the risk of postpartum haemorrhage or the need for blood transfusion.